Self-concealment Influence on Addictive Behaviour, Suicidal Ideation, and Mental Health Among Drug Addicts from Sampled Rehabilitation Centres in the Coastal Region of Kenya - Anika, Alice A.; Lambert, Edward (European Journal of Applied Sciences, 2024)
This study investigates the impact of self-concealment on addictive behaviours, suicidal ideation, and mental health among drug addicts in rehabilitation centres located in the coastal regions of Kenya. Self-concealment, defined as the tendency to hide personal information and emotions, is hypothesized to exacerbate psychological distress and hinder recovery processes. Utilizing a mixed-methods approach, the research sampled 200 individuals undergoing rehabilitation, employing standardized questionnaires to assess levels of self-concealment, addiction severity, suicidal thoughts, and overall mental health status. Qualitative interviews provided deeper insights into the lived experiences of participants, highlighting the interplay between self-concealment and their struggles with addiction and mental health. Findings reveal a significant correlation between high levels of self-concealment and increased addictive behaviours, as well as elevated suicidal ideation. Participants who reported greater difficulty in expressing their emotions were more likely to engage in substance use as a coping mechanism, leading to a cycle of addiction and mental health deterioration. The qualitative data further illustrated how societal stigma and fear of judgment contributed to self-concealment, perpetuating feelings of isolation and hopelessness. This research underscores the need for targeted interventions that address self-concealment in therapeutic settings, promoting open communication and emotional expression among individuals in recovery. By fostering an environment of trust and support, rehabilitation programs can enhance mental health outcomes and reduce the risk of suicide among drug addicts in Kenya's coastal regions.